Palaeoenvironmental record of the Cal Maurici wetland sediment archive in Barcelona (NE Iberian Peninsula) between c. 6000 and 4000 cal. yr BP - Daura, Joan (2018)
This study presents the results of a multi-proxy analysis conducted to improve our understanding of the palaeoenvironmental conditions of the freshwater and brackish marshes of Cal Maurici (Barcelona, Spain) and the human impact on them during the mid-Holocene (6171–3891 cal. yr BP). The study integrates data from pollen, phytolith, diatom, charcoal, seeds and malacological analyses and helps to reconstruct the ecological conditions during the early establishment of farming communities in western Mediterranean facade. The results indicate a landscape dominated by Mediterranean vegetation with aquatic plants in the shallow marshes and well-developed forests in the nearby area, providing for the first time in the Holocene of NE Iberian Peninsula the palaeoecological conditions of deltaic areas. Ecofactual evidence indicates an initial landscape dominated by brackish marshes (6171–5773 cal. yr BP) in which Ruppia cf. maritima was predominant and human impact was low. Between 5026 and 4839 cal yr. BP, freshwater conditions expanded with an increase in Potamogeton sp. and the presence of Typha angustifolia and Spirogyra sp. algae with well-developed oak woodlands and deciduous trees in nearby areas. The expansion of evergreen forest occurred later (from 4960 to 4825 cal. yr BP until 3712 cal. yr BP), with the decline of deciduous woodland and the expansion of evergreen oaks, pinewoods, wild olive trees and box, coinciding with a period of increased human activity in the area. Additionally, the presence of marine resources at several archaeological excavation sites and domestic plants at Cal Maurici provides an opportunity to evaluate the interaction between earlier farmers and marine or deltaic ecosystems.